Becoming the gospel Paul, participation, and mission - Gorman, Michael J. 1955- (Grand Rapids, Michigan Cambridge, U.K. William B. Eerdmans Publishing Company, 2015)
Invitation: Becoming the gospel -- Paul and the mission of God -- Reading Paul missionally -- Becoming the gospel of faith(fulness), love, and hope: 1 Thessalonians -- Becoming and telling the story of Christ: Philippians -- Becoming the gospel of peace (I): overview -- Becoming the gospel of peace (II): Ephesians -- Becoming the justice of God: 1 & 2 Corinthians -- Becoming the gospel of God's justice/righteousness and glory: missional theosis in Romans -- Final reflections: Becoming the gospel (reprise)
The first detailed exegetical treatment of Paul's letters from the emerging discipline of missional hermeneutics, Michael Gorman's Becoming the Gospel argues that Paul's letters invite Christian communities both then and now to not merely believe the gospel but to become the gospel and, in doing so, to participate in the life and mission of God. Showing that Pauline churches were active public participants in and witnesses to the gospel, Gorman reveals the missional significance of various themes in Paul's letters. He also identifies select contemporary examples of mission in the spirit of Paul, inviting all Christians to practice Paul-inspired imagination in their own contexts.--Publisher
Invitation: becoming the gospelPaul and the mission of God -- Reading Paul missionally -- Becoming the gospel of faith, love, and hope: 1 Thessalonians -- Becoming and telling the story of Christ: Philippians -- Becoming the gospel of peace (I): overview -- Becoming the gospel of peace (II): Ephesians -- Becoming the justice of God: 1 & 2 Corinthians -- Becoming the gospel of God's justice/righteousness and glory: missional theosis in Romans -- Final reflections: becoming the gospel (reprise).
Includes bibliographical references (pages 306-321) and indexes
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc -- Bible; Missions -- Biblical teaching; Mission of the church -- Biblical teaching; Missions -- Biblical teaching; Mission of the church -- Biblical teaching; Mission of the church -- Biblical teaching; Missions -- Biblical teaching -- Criticism, interpretation, etc